Expression, characterization and structure elucidation of thermotolerant lipase with broad pH isolated from Antarctic Pseudomonas sp. strain AMS3 - Latip, Wahhida (2018)
Lipase is an enzyme that plays an important role in detergent, cosmetic and pharmaceutical industries. Lipase from Antarctic region has gained huge interest for industrial applications but was impaired due to the limited crystallographic and structural information. To maximize its full biocatalytic potentials, the understanding on the biochemical and structural features of this class of enzyme are imperative. Therefore, this research was conducted to isolate, express, characterize and determine the structure of lipase from an Antarctic bacteria via in silico and crystallographic approaches. In this study, the best lipolytic producing bacterium was identified as Pseudomonas sp. AMS3. The lipase gene was isolated from the reconstructed of genomic library. The positive colonies were verified as recombinant lipase producer using triolein and Rhodamine B agar plates. Recombinant plasmid analysis revealed an open reading frame (ORF) of 1353 nucleotides encoding 450 amino acids. The protein sequence has two domains, namely GST C and lipase domains at the N and C terminal, respectively. The gene encoding the AMS3 lipase was cloned into a pET 51b vector and heterologously expressed in E. coli BL21 (De3). The best expression condition for AMS3 lipase was at 0.5 mM IPTG, incubated at 20 °C and 12 h of induction time. The recombinant AMS3 lipase was purified using single step affinity chromatography with a 50% recovery and 1.52 fold purity. The molecular weight of the recombinant AMS3 lipase was estimated at ~60 kDa. Biochemical characterization of the lipase showed the enzyme work at a broad temperature profile of 10-70 °C and stable at 10-60 °C. The AMS3 lipase activity also exhibited a broad pH range of 5 to 10 and was activated in the presence of metal ions. The lipase was able to hydrolyze long chain lipid substrate with and without organic solvents. The AMS3 lipase was successfully crystallized using sitting drop method. The X-ray diffraction of the AMS3 lipase crystal was very poor, thus no crystal structure was able to be determined. In order to obtain the crystal structure, the AMS3 lipase was truncated at the N terminal domain based in the computational analysis. Molecular dynamic simulation revealed a flexible N-terminal domain possibly interfering with the crystallization process. The truncated AMS3 lipase was subcloned and express in E.coli BL21 (De3) .This truncated enzyme has an approximate molecular weight of ~45 kDa. The truncated AMS3 lipase has similar features with native except for pH profile whereby the lipase was most active at alkaline condition (pH 8-pH 10). The truncated AMS3 lipase was successfully crystallized using sitting drop method and the crystal was diffracted to 2.7 Å. The 3D structure was refined, validated and deposited to Protein Data Bank (PDB no. 5XPX). The refined truncated AMS3 lipase structure revealed a common α/β hydrolase fold with bound calcium and zinc ions. The protein active site contained serine hydrolase catalytic triad, namely serine, aspartic acid and histidine. Superposition of the lipase thermostable homologs showed structural differences that could be potentially important towards the lipase temperature adaptation. It was generally concluded, the reduction of hydrogen bond and changes to the secondary structure content of the lipase allowed the enzyme to be active at broad temperatures. The structural and biochemical information will be beneficial towards rational design of lipase suitable for industrial application.